PENGARUH KUALITAS PELAYANAN AKADEMIK DAN CITRA INSTITUSI TERHADAP KEPUASAN MAHASISWA LP3I CILEGON - Subagiyo Subagiyo (POLITEKNIK LP3I JAKARTA, 2015)
The title of this research is The Influence Of Academic Service Quality And Corporate Image Towards Students’ Satisfaction at LP3I Cilegon. The objectives of this research was to know The Influence Of Academic Service Quality And Corporate Image Towards Students’ Satisfaction at LP3I Cilegon. The research was quantitative research and the population of this research were students of LP3I Cilegon who were in the first year (level I) with the total number of the population were 295 students. This research used purposes sampling method. The criteria of the sample were the students in the first year at academic year 2014 and the total respondents were 100 respondents. The analysis technique was multiple linear regressions. The result showed that the quality of the academic service and corporate image partially and simultaneously/ together influenced the students’ satisfaction Key words: academic service quality, corporate image and students’ satisfaction